The role of Environmental Innovation in enhancing the firm performance - Teh, Boon Heng (International Journal of Psychosocial Rehabilitation, 2020)
Company environmental practices are able to create competitive advantage, which in turn enhances their performance. However, environmental practices are expensive and complex to realise the expected benefits, and require effective implementation, thus making them a risky proposition with high failure rate. Thus, it is essential for the company to identify the truly environmental ca pabilities, for enhancing the company environmental competitive and financial performance. This research aims To capitalize the role of Environmental Innovation in enhancing the firm performance. In this study, a total of 124 responses were collected from managers of EMS14001 certified manufacturers in Malaysia, and data was subjected to a structural equation analysis using the Smart PLS version 3.2.7 software. Results endorse environmental innovation as the key enabler for the creation of economic values from environmental management i.e. environmental performance. This is owing to its function as the sole factor that directly contributes to firm performance. Moreover, environmental innovation is also found to be the full mediator that translates benefits of environmental performance into financial performance.